Characterization of bioploymers produced from different blends of chemically modified starch and natural rubber latex - Kiing, Sie Cheong (2011)
Development of biodegradable polymers from absolute environmental friendly materials has attracted increasing research interest due to public awareness of waste disposal problems with low degradable conventional plastic. In this study, starch and natural rubber latex which abundant, were assessed for their potential in making biodegradable polymers. Sago starch and rice starch with low and high amylose contents were chosen and chemically modified via acetylation and hydroxypropylation. Starches with and without chemical treatments were gelatinized and later casted with natural rubber latex in the following ratios 100.00/0.00, 99.75/1.25, 98.50/2.50, 95.00/5.00, 90.00/10.00 and 80.00/20.00 wt/wt, for preparing biopolymer films using solution spreading technique. The products were evaluated according to their water absorption, mechanical, thermal, morphological and biodegradable properties. Level of substitution showed that starches were successfully chemical modified. Acetylation of sago, LAR and HAR gave result of DS 1.05, 1.35 and 1.30 respectively. Hydroxypropylation of sago, LAR and HAR gave result of MS 0.13, 0.27 and 0.31 respectively. FTIR (Fourier Transform Infrared) analysis proved that acetyl and hydroxypropyl groups were successfully substituted into the starch macrostructures after the chemical substitutions. These substitutions improved starch water solubility and their compatibility with natural rubber latex in the film fabricating process via solution casting. Modifications of starches by either acetylation or hydroxypropylation increase water absorption ability of product films about 2 to 5 times higher compare to native starch product films. In terms of compatibility with natural rubber latex, high amylose rice, native and acetylated sago starch proved to be compatible and had good adhesion with natural rubber latex through SEM result. However, both modification modes did not exhibit differences trend in their thermal profile. Sago starch and rice starch product films showed similar trend of thermal and mechanical properties. Product films formulated from sago starch absorbed less water as compared to rice starch. Native sago starch product film showed 110% in water absorption capacity. However, native LAR and HAR product films showed 190 and 300% in water absorption capacity. Water absorption capacity of all type of biopolymer was able to reduce up to 95% when addition of natural rubber latex concentration reached 20%. Addition of natural rubber latex delayed biodegradable threshold of product films, but they were still completely biodegradable in the natural environment. Product films with less than 2.5% natural rubber content was totally biodegraded within 2 to 6 weeks. However, as concentration of natural rubber latex increase to 20%, biodegradability of the film still achieved 50% within 12 weeks. Product films with high natural rubber latex content exhibit high melting temperatures, inhibited the absorption of water and increased elongation at break. From the analysis of product films, it can be concluded that the ratio of the starch to natural rubber latex, selection of chemical substitution modes and types of starch played an important role in determining characteristics of final product blends. Biopolymer films with desirable properties can be fabricated by choosing an appropriate casting formulation.